A kind of cholecalciferol powder and preparation method thereof

By preparing cholecalciferol powder, using specific coating materials and modified microcrystalline cellulose, the problem of the decrease in the content of cholecalciferol products during storage and use is solved, and efficient antioxidant and prevention is achieved Hygroscopicity ensures the self-stability of the product and market prospects.

CN118662451BActive Publication Date: 2025-02-18QINGDAO CONSON PHARMACEUTICAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410551015.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-06
Publication Date
2025-02-18
Estimated Expiration
2044-05-06

AI Technical Summary

Technical Problem

Due to the instability and oxidation of existing cholecalciferol products, their content during storage and use has decreased and cannot meet quality standards.

Method used

By preparing a cholecalciferol powder, using a combination of specific coating materials, weight-average molecular weight control of polyvinyl alcohol and a technical solution of combining amylose and amylopectin, combined with modified microcrystalline cellulose as a carrier Particles improve the antioxidant, waterproof and hygroscopic and self-stability of the powder.

Benefits of technology

The stability and uniformity of the cholecalciferol content in cholecalciferol powder is achieved, its antioxidant and anti-hygroscopic properties are improved, the self-stability of the powder during storage and use is ensured, and the market demand is met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to the field of pharmaceutical powders, and in particular to a cholecalciferol powder and a preparation method thereof. The raw materials of the cholecalciferol powder include, by mass percentage, 0.05-1% cholecalciferol, 0.1-2% flow aid, 40-60% coating material, 20-30% carrier particles, 1-5% functional additives, and solvent to supplement the remainder. The cholecalciferol powder prepared in the present application can not only ensure that the content and uniformity of cholecalciferol therein meet the standards, but also ensure that it has excellent antioxidant properties and water-resistant and hygroscopic properties, and has extremely strong self-stability in use, transportation and storage, and has a very excellent market prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of pharmaceutical powders, and in particular to a cholecalciferol powder and a preparation method thereof. Background Art

[0002] Cholecalciferol, also known as vitamin D3, is a fat-soluble vitamin. It is regarded as a hormone precursor for calcium and phosphorus metabolism. It can maintain normal metabolism of calcium and phosphorus, thereby promoting the body's absorption of calcium and phosphorus.

[0003] Cholecalciferol is mainly synthesized by the human body, and the synthesis method requires the human body to be exposed to sunlight. However, due to the increase in skin cancer caused by ultraviolet radiation, air pollution, and weather changes in various regions, the time people in various countries receive sunlight is decreasing, resulting in a lack of cholecalciferol in the human body. Therefore, increasing the content of cholecalciferol in the human body by directly consuming cholecalciferol has become the most direct and effective way to deal with the above problems in recent years.

[0004] In the existing intake method, due to the light instability of cholecalciferol itself and its easy oxidation in the air, the content of cholecalciferol in the final intake product will be significantly reduced, and may not actually meet the content standard. Therefore, it is very necessary to provide a pharmaceutical product that can fully ensure the sufficient content of cholecalciferol in the finished product.

[0005] In order to solve the above problems, the present application provides a cholecalciferol powder and a preparation method thereof. The cholecalciferol powder prepared in the present application can not only ensure that the content and uniformity of cholecalciferol therein meet the standards, but also ensure that it has excellent antioxidant properties and waterproof and hygroscopic properties, and has extremely strong self-stability in use, transportation and storage, and has a very excellent market prospect. Summary of the invention

[0006] In order to solve the above problems, the first aspect of the present application provides a cholecalciferol powder, in which the raw materials include, by mass percentage: 0.05~1% cholecalciferol, 0.1~2% glidant, 40~60% coating material, 20~30% carrier particles, 1~5% functional additives, and solvent to supplement the balance.

[0007] As a preferred embodiment, the mass ratio of cholecalciferol, coating material and carrier particles is (0.05-0.5): (50-60): (25-30).

[0008] As a preferred embodiment, the mass ratio of cholecalciferol, coating material and carrier particles is (0.25-0.5): (50-55): 25.

[0009] As a preferred solution, the glidant is at least one of silicon dioxide, aluminum silicate and zinc stearate.

[0010] As a preferred solution, the flow aid is silicon dioxide or aluminum silicate.

[0011] As a preferred solution, the mass ratio of the carrier particles to the flow aid is (25-30): (0.5-1.5).

[0012] As a preferred solution, the mass ratio of the carrier particles to the flow aid is 25:1.

[0013] As a preferred solution, the coating material is at least one of sucrose, starch ester, starch, hydroxypropyl methylcellulose, chitosan, gelatin, carrageenan, gum arabic, hydroxypropyl cellulose, polyvinyl alcohol, cellulose acetate, and ethyl cellulose.

[0014] As a preferred solution, the coating material is starch, starch ester and polyvinyl alcohol.

[0015] As a preferred solution, the mass ratio of the starch, starch ester and polyvinyl alcohol is (1-2):(4-6):(0.5-2).

[0016] As a preferred solution, the mass ratio of the starch, starch ester and polyvinyl alcohol is (1-1.5):5.5:1.

[0017] As a preferred solution, the starch ester is octenyl succinate starch ester.

[0018] As a preferred solution, the starch is a composition of amylose and amylopectin.

[0019] As a preferred solution, the mass ratio of the straight-chain starch to the amylopectin is (3-4): (0.2-0.5).

[0020] As a preferred solution, the mass ratio of the amylose to the amylopectin is (3.5-3.8): (0.3-0.4).

[0021] As a preferred solution, the weight average molecular weight of the polyvinyl alcohol is 50,000-200,000.

[0022] As a preferred solution, the weight average molecular weight of the polyvinyl alcohol is 80,000-100,000.

[0023] In the present application, by means of the technical solution of compounding and mixing the above-mentioned specific coating materials, controlling the weight average molecular weight of polyvinyl alcohol, and using a combination of amylose and amylopectin at the same time, the antioxidant property of cholecalciferol powder is effectively improved, and its self-stability and anti-hygroscopic property are further improved. When the above-mentioned solution is adopted, the added octenyl succinate starch ester and polyvinyl alcohol can form an entanglement interface with amylose having a long helical complex linear structure through the multi-branched molecular segments of amylopectin. The existence of this interface not only greatly enhances the coating effect of the coating material on cholecalciferol, but also can form a good barrier and steric effect in the overall powder system. In the multi-layer protective film structure formed by different molecular segments, the movement and migration efficiency of active molecules and water molecules in the powder system can be effectively inhibited, thereby reducing the collision frequency and intensity between active molecules, greatly reducing the probability of active reactions, and forming a strong barrier interface to prevent excessive intrusion of water, so that the powder can maintain excellent antioxidant properties under various environments while also having excellent anti-hygroscopic and self-stability.

[0024] As a preferred solution, the carrier particles are at least one of lactose, microcrystalline cellulose, maltodextrin, cyclodextrin, mannitol and sorbitol.

[0025] As a preferred solution, the carrier particles are modified microcrystalline cellulose.

[0026] As a preferred scheme, the preparation method of the modified microcrystalline cellulose comprises the following steps: S1: treating the fibrous microcrystalline cellulose with a 10wt% sodium hydroxide solution for 3-5min, and then washing, filtering, drying and mixing the treated fibrous microcrystalline cellulose with deionized water; S2: then adding sodium carboxymethyl cellulose, polyethylene glycol 800 and phytic acid, controlling the stirring speed to 200-300rpm, and the stirring time to 30-40min; S3: after the stirring is completed, adding dropwise anhydrous ethanol solution containing ethyl orthosilicate, the dropwise reaction time is 2h, after the dropwise addition is completed, heating to 50-60°C, adding succinic anhydride and 3-aminopropyltriethoxysilane, reacting for 2-4h, filtering, washing and drying after the reaction is completed to obtain the modified microcrystalline cellulose.

[0027] As a preferred embodiment, the diameter of the fibrous microcrystalline cellulose is 15-20 nm.

[0028] As a preferred solution, the length of the fibrous microcrystalline cellulose is 100-200 μm.

[0029] As a preferred solution, the amount of the anhydrous ethanol solution containing ethyl orthosilicate added is 20-40wt% of the product obtained in S2.

[0030] As a preferred solution, the mass ratio of tetraethyl orthosilicate to fibrous microcrystalline cellulose is (5-10): (35-40).

[0031] As a preferred embodiment, the mass ratio of the fibrous microcrystalline cellulose to sodium carboxymethyl cellulose, polyethylene glycol 800 and phytic acid is (30-40): (4-5): (0.1-0.5): (2-3).

[0032] As a preferred solution, the mass ratio of succinic anhydride to 3-aminopropyltriethoxysilane is (3-4):1.

[0033] In the present application, by adding the modified microcrystalline cellulose as carrier particles, the self-stability of the powder prepared in the present application can be significantly improved, and it has very excellent storage moisture and moisture absorption performance. The modified microcrystalline cellulose in the present application can form a good staggered friction interface with the long straight curly and multi-branched chain structure of starch in the coating material system more quickly, thereby effectively improving the interfacial stress between the internal raw materials, thereby forming a more narrow molecular chain spacing at the microscopic level, greatly limiting the migration speed of water molecules in the colloid system, and at the same time significantly reducing the activity of active groups and active molecules, reducing the frequency and reaction rate of related substance reactions, and further processing steps for the surface of microcrystalline cellulose can also enhance its connection force with the coating material, thereby effectively forming a protective hydrophobic layer on the surface of the powder to reduce water penetration.

[0034] As a preferred solution, the functional auxiliary agent is at least one of an anti-caking agent, an anti-hygroscopic agent, an antioxidant, a light-resistant agent, a dispersant, a wetting agent, a surfactant, and a plasticizer.

[0035] As a preferred solution, the functional additives are anti-caking agents, antioxidants and plasticizers.

[0036] As a preferred solution, the mass ratio of the anti-caking agent, antioxidant and plasticizer is (1~2): (1~2): (1~2).

[0037] As a preferred solution, the anti-caking agent is at least one of stearic acid, magnesium stearate, sodium stearate and povidone.

[0038] As a preferred solution, the anti-caking agent is magnesium stearate.

[0039] As a preferred solution, the antioxidant is at least one of butylated hydroxytoluene, ascorbic acid, ascorbyl palmitate, and butylated hydroxyanisole.

[0040] As a preferred embodiment, the antioxidant is ascorbyl palmitate.

[0041] As a preferred solution, the plasticizer is a combination of polyethylene glycol 200 and polyethylene glycol 1200.

[0042] As a preferred solution, the mass ratio of polyethylene glycol 200 to polyethylene glycol 1200 is (0.5-1): (3-4.5).

[0043] As a preferred solution, the solvent is at least one of cottonseed oil, peanut oil, sesame oil and soybean oil.

[0044] As a preferred solution, the solvent is peanut oil.

[0045] The second aspect of the present application provides a method for preparing the above-mentioned cholecalciferol powder, which comprises the following steps: S1: adding the coating material to purified water, heating it to 60-65°C and stirring it evenly to obtain a coating solution for use; S2: mixing the remaining other raw materials, heating them to 50-60°C, stirring them evenly at a speed of 60-200r / min, then adding the coating solution, stirring and homogenizing, and drying after completion until the material LOD is ≤3%.

[0046] The beneficial effects of this application are:

[0047] 1. The cholecalciferol powder provided in the present application can not only ensure that the content and uniformity of cholecalciferol therein meet the standards, but also ensure that it has excellent antioxidant and waterproof hygroscopic properties, has extremely strong self-stability in use, transportation and storage, and has very excellent market prospects.

[0048] 2. A cholecalciferol powder provided in the present application, through the limitation of the technical scheme of compounding and mixing specific coating materials, controlling the weight-average molecular weight of polyvinyl alcohol and simultaneously using a combination of amylose and amylopectin, effectively improves the antioxidant property of the cholecalciferol powder while further improving its self-stability and anti-hygroscopicity; the added octenyl succinate starch ester and polyvinyl alcohol can form an entanglement interface with amylose having a long helical complex linear structure through the multi-branched molecular segments of amylopectin, and the existence of this interface not only greatly enhances the coating effect of the coating material on cholecalciferol, but also can form a good barrier and steric hindrance in the overall powder system, and in the multi-layer protective film structure formed by different molecular segments, the movement and migration efficiency of active molecules and water molecules in the powder system can be effectively inhibited, thereby greatly enhancing its own stability and the migration resistance to water molecules.

[0049] 3. The cholecalciferol powder provided in the present application can significantly improve the self-stability of the powder prepared in the present application by adding the above-mentioned modified microcrystalline cellulose as carrier particles, and has very excellent storage moisture and hygroscopic properties; the modified microcrystalline cellulose can form a good staggered friction interface with the long straight curly and multi-branched chain structure of starch in the coating material system more quickly, thereby effectively increasing the interfacial stress between the internal raw materials, thereby forming a finer and narrower molecular chain spacing at the microscopic level, greatly limiting the migration speed of water molecules in the colloid system, and at the same time significantly reducing the activity of active groups and active molecules, reducing the frequency and reaction rate of related substance reactions, and further processing steps on the surface of microcrystalline cellulose can also enhance its connection force with the coating material, thereby effectively forming a protective hydrophobic layer on the surface of the powder to reduce water penetration.

[0050] 4. The cholecalciferol powder provided in the present application has simple and readily available raw materials for preparation, a simple preparation method, no complicated chemical reactions involved, and no obvious corrosion to the preparation equipment. Therefore, in subsequent large-scale production, the labor and equipment maintenance costs of production can be effectively controlled, and it has excellent market economic prospects. DETAILED DESCRIPTION

[0051] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.

[0052] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.

[0053] Example 1

[0054] Example 1 The first aspect provides a cholecalciferol powder, in which the raw materials include, by mass percentage: 0.35% cholecalciferol, 1% glidant, 55% coating material, 25% carrier particles, 5% functional additives, and the remainder is supplemented by solvent.

[0055] The flow aid is silicon dioxide with an average particle size of 50 nm.

[0056] The coating materials are starch, starch ester and polyvinyl alcohol in a mass ratio of 1:5.5:1.

[0057] The starch ester is octenyl succinate starch ester, a food-grade product purchased from Wuhan Huaxiang Kejie Biotechnology Co., Ltd.; the weight-average molecular weight of polyvinyl alcohol is 100,000, purchased from a product of corresponding molecular weight sold by Wuhan Runxing Technology Co., Ltd.; the starch is a composition of amylose and amylopectin, with a mass ratio of 3.6:0.4, and the amylose and amylopectin are purchased from premium-grade products sold by Wuhan Huaxiang Kejie Biotechnology Co., Ltd.

[0058] The carrier particles are modified microcrystalline cellulose; the preparation method of the modified microcrystalline cellulose comprises the following steps (by mass): S1: treating 35 parts of fibrous microcrystalline cellulose with 20 parts of 10wt% sodium hydroxide solution for 5 minutes, and then washing, filtering, drying and mixing the treated microcrystalline cellulose with 250 parts of deionized water; S2: then adding 5 parts of sodium carboxymethyl cellulose, 0.5 parts of polyethylene glycol 800 and 3 parts of phytic acid, controlling the stirring speed to 200rpm, and stirring time to 40min; S3: after stirring, adding dropwise anhydrous ethanol solution containing 5 parts of ethyl orthosilicate (the amount added is 30wt% of the product obtained in S2), the dropwise reaction time is 2h, after the dropwise addition is completed, heating to 55°C, adding 8 parts of succinic anhydride and 2 parts of 3-aminopropyltriethoxysilane, reacting for 3h, filtering, washing and drying after the reaction is completed, and obtaining the modified microcrystalline cellulose.

[0059] The fibrous microcrystalline cellulose had a diameter of 20 nm and a length of 150 μm and was purchased from Guangzhou Huayu Biotechnology Co., Ltd.

[0060] The functional additives are anti-caking agent, antioxidant and plasticizer, and the mass ratio of the three is 1:1:1.

[0061] The anti-caking agent is magnesium stearate; the antioxidant is ascorbyl palmitate; and the plasticizer is a combination of polyethylene glycol 200 and polyethylene glycol 1200, with the mass ratio of the two being 1:4.

[0062] The solvent is peanut oil.

[0063] The second aspect of the present embodiment provides a method for preparing the above-mentioned cholecalciferol powder, which comprises the following steps: S1: adding the coating material to purified water, heating it to 65°C and stirring it evenly to obtain a coating solution for use; S2: mixing the remaining other raw materials, heating them to 55°C, stirring them evenly at a speed of 120r / min, then adding the coating solution, stirring and homogenizing, and drying after completion until the material LOD ≤ 3%.

[0064] Example 2

[0065] Example 2 The first aspect provides a cholecalciferol powder, in which the raw materials include, by mass percentage: 0.4% cholecalciferol, 1.5% glidant, 50% coating material, 30% carrier particles, 5% functional additives, and solvent to supplement the balance.

[0066] The flow aid is silicon dioxide with an average particle size of 50 nm.

[0067] The coating materials are starch, starch ester and polyvinyl alcohol in a mass ratio of 1:5.5:1.

[0068] The starch ester is octenyl succinate starch ester, a food-grade product purchased from Wuhan Huaxiang Kejie Biotechnology Co., Ltd.; the weight-average molecular weight of polyvinyl alcohol is 100,000, purchased from a product of corresponding molecular weight sold by Wuhan Runxing Technology Co., Ltd.; the starch is a composition of amylose and amylopectin, with a mass ratio of 3.6:0.4, and the amylose and amylopectin are purchased from premium-grade products sold by Wuhan Huaxiang Kejie Biotechnology Co., Ltd.

[0069] The carrier particles are modified microcrystalline cellulose; the preparation method of the modified microcrystalline cellulose comprises the following steps (by mass): S1: treating 35 parts of fibrous microcrystalline cellulose with 20 parts of 10wt% sodium hydroxide solution for 5 minutes, and then washing, filtering, drying and mixing the treated microcrystalline cellulose with 250 parts of deionized water; S2: then adding 5 parts of sodium carboxymethyl cellulose, 0.5 parts of polyethylene glycol 800 and 3 parts of phytic acid, controlling the stirring speed to 200rpm, and stirring time to 40min; S3: after stirring, adding dropwise anhydrous ethanol solution containing 5 parts of ethyl orthosilicate (the amount added is 30wt% of the product obtained in S2), the dropwise reaction time is 2h, after the dropwise addition is completed, heating to 55°C, adding 8 parts of succinic anhydride and 2 parts of 3-aminopropyltriethoxysilane, reacting for 3h, filtering, washing and drying after the reaction is completed, and obtaining the modified microcrystalline cellulose.

[0070] The fibrous microcrystalline cellulose had a diameter of 20 nm and a length of 150 μm and was purchased from Guangzhou Huayu Biotechnology Co., Ltd.

[0071] The functional additives are anti-caking agent, antioxidant and plasticizer, and the mass ratio of the three is 1:1:1.

[0072] The anti-caking agent is magnesium stearate; the antioxidant is ascorbyl palmitate; and the plasticizer is a combination of polyethylene glycol 200 and polyethylene glycol 1200, with the mass ratio of the two being 1:4.

[0073] The solvent is peanut oil.

[0074] The second aspect of the present embodiment provides a method for preparing the above-mentioned cholecalciferol powder, which comprises the following steps: S1: adding the coating material to purified water, heating it to 65°C and stirring it evenly to obtain a coating solution for use; S2: mixing the remaining other raw materials, heating them to 55°C, stirring them evenly at a speed of 120r / min, then adding the coating solution, stirring and homogenizing, and drying after completion until the material LOD ≤ 3%.

[0075] Example 3

[0076] Example 3 The first aspect provides a cholecalciferol powder, in which the raw materials include, by mass percentage: 0.35% cholecalciferol, 1% glidant, 55% coating material, 25% carrier particles, 5% functional additives, and solvent to supplement the balance.

[0077] The flow aid is silicon dioxide with an average particle size of 80 nm.

[0078] The coating materials are starch, starch ester and polyvinyl alcohol in a mass ratio of 1:6:0.8.

[0079] The starch ester is octenyl succinate starch ester, a food-grade product purchased from Wuhan Huaxiang Kejie Biotechnology Co., Ltd.; the weight-average molecular weight of polyvinyl alcohol is 80,000, purchased from a product of corresponding molecular weight sold by Wuhan Runxing Technology Co., Ltd.; the starch is a composition of amylose and amylopectin, with a mass ratio of 3.5:0.5, and the amylose and amylopectin are purchased from premium-grade products sold by Wuhan Huaxiang Kejie Biotechnology Co., Ltd.

[0080] The carrier particles are modified microcrystalline cellulose; the preparation method of the modified microcrystalline cellulose comprises the following steps (by mass): S1: treating 35 parts of fibrous microcrystalline cellulose with 20 parts of 10wt% sodium hydroxide solution for 5 minutes, and then washing, filtering, drying and mixing the treated microcrystalline cellulose with 250 parts of deionized water; S2: then adding 5 parts of sodium carboxymethyl cellulose, 0.5 parts of polyethylene glycol 800 and 3 parts of phytic acid, controlling the stirring speed to 200rpm, and stirring time to 40min; S3: after stirring, adding dropwise anhydrous ethanol solution containing 5 parts of ethyl orthosilicate (the amount added is 30wt% of the product obtained in S2), the dropwise reaction time is 2h, after the dropwise addition is completed, heating to 55°C, adding 8 parts of succinic anhydride and 2 parts of 3-aminopropyltriethoxysilane, reacting for 3h, filtering, washing and drying after the reaction is completed, and obtaining the modified microcrystalline cellulose.

[0081] The fibrous microcrystalline cellulose had a diameter of 15 nm and a length of 200 μm and was purchased from Guangzhou Huayu Biotechnology Co., Ltd.

[0082] The functional additives are anti-caking agent, antioxidant and plasticizer, and the mass ratio of the three is 1:1:1.

[0083] The anti-caking agent is magnesium stearate; the antioxidant is ascorbyl palmitate; and the plasticizer is a combination of polyethylene glycol 200 and polyethylene glycol 1200, with the mass ratio of the two being 1:4.

[0084] The solvent is peanut oil.

[0085] The second aspect of the present embodiment provides a method for preparing the above-mentioned cholecalciferol powder, which comprises the following steps: S1: adding the coating material to purified water, heating it to 65°C and stirring it evenly to obtain a coating solution for use; S2: mixing the remaining other raw materials, heating them to 55°C, stirring them evenly at a speed of 120r / min, then adding the coating solution, stirring and homogenizing, and drying after completion until the material LOD ≤ 3%.

[0086] Comparative Example 1

[0087] The specific implementation of this comparative example is basically the same as that of Example 1, except that the coating materials are starch, starch ester and polyvinyl alcohol in a mass ratio of 0.5:8:0.1; and the starch is straight-chain starch.

[0088] Comparative Example 2

[0089] The specific implementation of this comparative example is basically the same as that of Example 1, except that the starch is a composition of amylose and amylopectin, and the mass ratio of the amylose and amylopectin is 1:1.

[0090] Comparative Example 3

[0091] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of modified microcrystalline cellulose comprises the following steps (in parts by mass): S1: treating 35 parts of fibrous microcrystalline cellulose with 20 parts of 10wt% sodium hydroxide solution for 5 minutes, and then washing, filtering, drying and mixing the treated microcrystalline cellulose with 250 parts of deionized water; S2: then adding 5 parts of sodium carboxymethyl cellulose, 0.5 parts of polyethylene glycol 800 and 3 parts of phytic acid, controlling the stirring speed to 200rpm, the stirring time to 40min, filtering, washing and drying after the reaction is completed to obtain modified microcrystalline cellulose.

[0092] Comparative Example 4

[0093] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of modified microcrystalline cellulose comprises the following steps (in parts by mass): S1: treating 35 parts of fibrous microcrystalline cellulose with 20 parts of 10wt% sodium hydroxide solution for 5 minutes, and then washing, filtering, drying and mixing the treated microcrystalline cellulose with 250 parts of deionized water; S2: then adding 2 parts of sodium carboxymethyl cellulose, 10 parts of polyethylene glycol 800 and 1 part of phytic acid, controlling the stirring speed to 200rpm, and stirring time to 40min; S3: after stirring, adding dropwise anhydrous ethanol solution containing 15 parts of ethyl orthosilicate (the amount added is 30wt% of the product obtained in S2), the dropwise reaction time is 2h, after the dropwise addition is completed, heating to 55°C, adding 8 parts of succinic anhydride and 2 parts of 3-aminopropyltriethoxysilane, reacting for 3h, filtering, washing and drying after the reaction is completed to obtain modified microcrystalline cellulose.

[0094] Comparative Example 5

[0095] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of modified microcrystalline cellulose comprises the following steps (in parts by mass): S1: treating 10 parts of fibrous microcrystalline cellulose with 20 parts of 10wt% sodium hydroxide solution for 5 minutes, and then washing, filtering, drying and mixing the treated microcrystalline cellulose with 250 parts of deionized water; S2: then adding 8 parts of sodium carboxymethyl cellulose, 0.1 parts of polyethylene glycol 800 and 0.1 parts of phytic acid, controlling the stirring speed to 200rpm, and stirring time to 40min; S3: after stirring, adding dropwise anhydrous ethanol solution containing 10 parts of ethyl orthosilicate (the amount added is 20wt% of the product obtained in S2), the dropwise reaction time is 2h, after the dropwise addition is completed, heating to 55°C, adding 2 parts of succinic anhydride and 5 parts of 3-aminopropyltriethoxysilane, reacting for 3h, filtering, washing and drying after the reaction is completed to obtain modified microcrystalline cellulose.

[0096] Comparative Example 6

[0097] The specific implementation of this comparative example is basically the same as that of Example 1, except that the microcrystalline cellulose is granular microcrystalline cellulose with a diameter of 25 μm, purchased from Chengdu Wanxiang Hongrun Biotechnology Co., Ltd.

[0098] Comparative Example 7

[0099] The specific implementation of this comparative example is basically the same as that of Example 1, except that the plasticizer is polyethylene glycol 2000.

[0100] Performance Evaluation

[0101] Anti-hygroscopicity test: The cholecalciferol powders prepared in the examples and comparative examples were subjected to an anti-hygroscopicity test. The moisture content of the test powder sample was experimentally obtained before the test, and then the powder sample was placed in a constant temperature and humidity chamber at a temperature of 50°C and a humidity of 75% for 14 days. The moisture content of the powder sample was measured after it was taken out, and the percentage increase in moisture content was recorded. The percentage increase in moisture content = moisture content after the test - moisture content before the test, and the average value of 10 measured values ​​was recorded in Table 1.

[0102] Powder stability: The cholecalciferol powders prepared in the examples and comparative examples were subjected to stability tests. The test powder samples were placed in a constant temperature and humidity chamber at a temperature of 60° C. and a humidity of 75% for 14 days to observe whether there was obvious discoloration. The results are recorded in Table 1.

[0103] Angle of repose: The cholecalciferol powders prepared in the examples and comparative examples were tested for angle of repose, and the average values ​​of 10 measurements were recorded in Table 1.

[0104] Relative content: The cholecalciferol powders prepared in the examples and comparative examples were tested for relative content, and the average values ​​of 10 times were recorded in Table 1.

[0105] Table 1

[0106]

[0107] From the examples and comparative examples of the present application and the data results in Table 1, it can be seen that Examples 1 to 3, which adopt the necessary technical solutions given in the present application, have achieved excellent results in terms of powder stability, anti-hygroscopicity and repose angle, which enables them to effectively replace existing cholecalciferol powder products and solve the technical problems of poor stability and substandard content of existing cholecalciferol products. However, since Comparative Examples 1 to 7 do not fully adopt the necessary technical solutions described by the applicant, their corresponding test results are significantly worse than Examples 1 to 3, which better proves the irreplaceable nature of the specific technical solutions of the present application in achieving technical effects and solving technical problems.

Claims

1. A cholecalciferol powder, characterized in that: In terms of mass percentage, the raw materials include: 0.05-1% cholecalciferol, 0.1-2% flow aid, 40-60% coating material, 20-30% carrier particles, 1-5% functional additives, and the remainder is supplemented by solvent; The mass ratio of cholecalciferol, coating material and carrier particles is (0.05-0.5): (50-60): (25-30); The glidant is at least one of silicon dioxide, aluminum silicate, and zinc stearate; The mass ratio of the carrier particles to the flow aid is (25-30): (0.5-1.5); The coating material is starch, starch ester and polyvinyl alcohol; The mass ratio of the starch, starch ester and polyvinyl alcohol is (1-2): (4-6): (0.5-2); The starch ester is octenyl succinate starch; The starch is a composition of amylose and amylopectin; the mass ratio of amylose to amylopectin is (3-4): (0.2-0.5); The carrier particles are modified microcrystalline cellulose; the preparation method of the modified microcrystalline cellulose comprises the following steps: S1: treating the fibrous microcrystalline cellulose with a 10wt% sodium hydroxide solution for 3-5min, and then washing, filtering, drying and mixing the treated fibrous microcrystalline cellulose with deionized water; S2: then adding sodium carboxymethyl cellulose, polyethylene glycol 800 and phytic acid, controlling the stirring speed to 200-300rpm, and the stirring time to 30-40min; S3: after the stirring is completed, adding dropwise anhydrous ethanol solution containing ethyl orthosilicate, the dropwise reaction time is 2h, after the dropwise addition is completed, heating to 50-60°C, adding succinic anhydride and 3-aminopropyltriethoxysilane, reacting for 2-4h, filtering, washing and drying after the reaction is completed, and obtaining the modified microcrystalline cellulose; The mass ratio of the fibrous microcrystalline cellulose to sodium carboxymethyl cellulose, polyethylene glycol 800 and phytic acid is (30-40): (4-5): (0.1-0.5): (2-3); the diameter of the fibrous microcrystalline cellulose is 15-20 nm; the length of the fibrous microcrystalline cellulose is 100-200 μm; The functional additives are anti-caking agents, antioxidants and plasticizers; The mass ratio of the anti-caking agent, antioxidant and plasticizer is (1-2): (1-2): (1-2); The anti-caking agent is magnesium stearate; the antioxidant is ascorbyl palmitate; The plasticizer is a composition of polyethylene glycol 200 and polyethylene glycol 1200; the mass ratio of polyethylene glycol 200 to polyethylene glycol 1200 is (0.5-1): (3-4.5).

2. The cholecalciferol powder according to claim 1, characterized in that: The mass ratio of the cholecalciferol, the coating material and the carrier particles is (0.25-0.5): (50-55):

25.

3. The cholecalciferol powder according to claim 2, characterized in that: The flow aid is silicon dioxide or aluminum silicate.

4. A method for preparing the cholecalciferol powder according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: S1: adding the coating material to purified water, heating it to 60-65°C and stirring evenly to obtain a coating solution for use; S2: mixing the remaining other raw materials, heating them to 50-60°C, stirring evenly at a speed of 60-200r / min, then adding the coating solution, stirring and homogenizing, and drying after completion until the material LOD is ≤3%.

Citation Information

Patent Citations

  • Preparation method of vitamin D3 tablet

    CN110151770A

  • Paricalcitol solid composition as well as preparation method and application thereof

    CN114948878A